(untitled) (المجلة الدولية للبحوث العلمية, 2024)
The assistant teacher has an important role to play in improving the educational process in the field of education. The purpose of the study was to learn about the role of the assistant teacher in improving the educational process from the point of view of the permanent teachers in the private education sector in Muscat governorate. The study was based on the analytical descriptive curriculum and was used as a tool for study. The school community included 100 kindergarten teachers. The results of this study have led to a high degree of calculation of the role of assistant teacher in the four areas (planning, implementation, evaluation, and human relations). This study produced several recommendations, notably the introduction of the assistant teacher program in public schools, which has a prominent role to play in raising and improving the quality of the educational process, together with the classroom teacher, and the delegation of many powers to carry out its roles properly and appropriately.